Implications of the Implementation of a Carbon Tax on Investment and Economic Growth in Indonesia - Rasji, Rasji; Effendi, Kevin Noble; Wafi, Auzan (CV. Rayyan Dwi Bharata, 2023)
Law Number 21 of 2021 concerning Harmonization of Tax Regulations is a form of renewal of various tax policies which has added a new tax object, namely carbon tax. However, the implementation of this regulation raises several problems, such as the increase in electricity prices that rely on Steam Powered Power Plants (PLTU), which can have an impact on companies' investment interest. Apart from that, the implementation of the carbon tax itself does not yet have a clear legal umbrella regarding setting emission limits, the percentage of emissions that can be traded and subject to carbon tax, and regulations related to the object and subject of the tax. The research analysis used is qualitative analysis, namely collecting data from various types of literature from which conclusions will then be obtained and become research results. The approach used is an empirical approach, namely looking at how the law operates in a society. Legal uncertainty surrounding carbon taxes and frequent policy changes can discourage investment. If companies feel uncertain about the future of carbon tax policy, this may influence investment decisions. So the Government needs to mitigate this, for example by considering compensation or incentive programs. Companies that invest in green technologies may be given tax incentives or financial assistance to mitigate the additional tax burden that may arise from a carbon tax